Characteristics of marine communities in the aftermath of the latest Permian mass extinction, Bank of Guizhou, South China - William J Foster; Daniel Lehrmann; Meiyi Yu; Li Ji; Rowan C Martindale (PANGAEA, 2018)
The aftermath of the late Permian mass extinction is a key interval for the evolution of modern marine ecosystems. It has been hypothesized that the magnitude of the mass extinction delayed the subsequent recovery, and so to test this, we undertook the highest resolution study to date of the post-extinction (Griesbachian) microbialite unit on the Great Bank of Guizhou, South China. The benthic community from the microbialite unit is taxonomically diverse when compared to other coeval deposits, recording both inarticulate and articulate brachiopods, crinoids, echinoids, bivalves, gastropods, microconchids, and ostracods. Here we recognize 49 taxa from 4557 individuals, which raise the known diversity of the Great Bank of Guizhou basal microbialite unit to 84 invertebrate species, making it the most diverse Early Triassic community currently reported. 89% of the genera are Permian holdovers, whilst only 13% of the species are Permian holdovers. This new data record no temporal trends in the species richness, Simpson diversity, Simpson effective diversity, taxonomic distinctness, functional diversity, or body size of the benthos during the post-extinction microbialite unit. Nevertheless, the small body sizes of the benthic community, and the large lophophoral cavity in the lingulid brachiopod, Sinolingularia huananensis, suggests that these animals lived in a highly stressed environment. We propose that the microbialite unit contains a survival fauna in an interval that represents persistent environmental stress from the late Permian mass extinction event, associated with deoxygenation, high temperatures, elevated atmospheric carbon dioxide levels (pCO2), and elevated primary productivity.
Supplement to: Foster, WJ et al. (2018): Persistent Environmental Stress Delayed the Recovery of Marine Communities in the Aftermath of the Latest Permian Mass Extinction. Paleoceanography and Paleoclimatology, 33(4), 338-353, https://doi.org/10.1002/2018PA003328